Peningkatan Kesejahteraan Keluarga Melalui Karakter Mujhid-Muzhid Menurut Prespektif Al-Qur’an dan Al-Hadist - Fatahillah, Wilnan; Gunawan, Tri (Lisyabab : Jurnal Studi Islam dan Sosial, 2024)
Family welfare is a significant issue in Indonesia, intertwined with the daily livelihood needs fulfillment. One approach to achieving family welfare is through the mujhid-muzhid character (hard work and frugality). This research aims to explain the terminology of mujhid-muzhid, uncover the guidance of the Qur'an and Hadith regarding it, and analyze this character in the context of realizing family welfare from the perspective of the Qur'an. A qualitative method was employed in this research, focusing on literature review. The findings highlight the importance of the mujhid-muzhid character in achieving family welfare. The research also identifies the crucial role of parents as role models in shaping this character in the younger generation, thereby fostering collective commitment to realizing family welfare through hard work and frugality in daily life.